2023
DOI: 10.1021/acs.macromol.2c02068
|View full text |Cite
|
Sign up to set email alerts
|

Dual Origin of Viscoelasticity in Polymer-Carbon Black Hydrogels: A Rheometry and Electrical Spectroscopy Study

Abstract: Nanocomposite gels formed by mixing nanoparticles and polymers offer a limitless creative space for the design of functional advanced materials with a broad range of applications in materials and biological sciences. Here, we focus on aqueous dispersions of hydrophobic colloidal soot particles, namely, carbon black (CB) dispersed with a sodium salt of carboxymethylcellulose (CMC), a food additive known as cellulose gum that bears hydrophobic groups, which are liable to bind physically to CB particles. Varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 112 publications
0
5
1
Order By: Relevance
“…Moreover, in the high-frequency limit, ω̃ 1 / 2 , which is reminiscent of the power-law rheology of critical gels and in remarkable agreement with a Rouse scaling. This high-frequency response also contrasts with the 2/3 scaling exponent reported for CMC (and polyacrylamide) hydrogels cross-linked by colloidal particles. ,, …”
contrasting
confidence: 74%
See 2 more Smart Citations
“…Moreover, in the high-frequency limit, ω̃ 1 / 2 , which is reminiscent of the power-law rheology of critical gels and in remarkable agreement with a Rouse scaling. This high-frequency response also contrasts with the 2/3 scaling exponent reported for CMC (and polyacrylamide) hydrogels cross-linked by colloidal particles. ,, …”
contrasting
confidence: 74%
“…This high-frequency response also contrasts with the 2/3 scaling exponent reported for CMC (and polyacrylamide) hydrogels cross-linked by colloidal particles. 24,28,29 To further elucidate the self-assembly of CMC upon acidification, we use small-angle neutron scattering (SANS) and report the scattering intensity spectra I(q) in Figure 3. For viscoelastic liquids, i.e., at pH > 3, the signal-to-noise ratio is low, and I(q) decays roughly as q −2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…150,152 In this sense, the fractional Maxwell gel is an exact mechanical analog to the Cole–Cole model 186 which has been historically used in modeling anomalous dielectric relaxation in complex materials. 151,154,158,187…”
Section: Fractional Mechanical Modelsmentioning
confidence: 99%
“…The similarity of the SAOS curves across the wide range of frequencies implies that there is structural similarity between carbon black gels prepared with different shear histories and different carbon black loadings. Legrand et al [19] recently showed that such similarity is violated upon addition of adsorbing polymer to the suspending medium or when the carbon black in the suspension is concentrated such that it forms a paste which incorporates capillary interfaces homogeneously distributed throughout its volume. SAOS is conducted in the linear viscoelastic region (LVR) where the microstructure remains unaltered by deformation.…”
Section: Quiescent Rheology Of Carbon Black Suspensionsmentioning
confidence: 99%